Pyrrhonian skepticism in Diogenes Laertius - Bett, Richard Arnot Home; Corti, Lorenzo; Olfert, Christiana M. M.; Sedley, D. N.; Vogt, Katja Maria, 1968- (Sapere (Darmstadt, Germany), 2015)
This volume offers the first bilingual edition of a major text in the history of epistemology, Diogenes Laertius's report on Pyrrho and Timon in his Lives of Eminent Philosophers. Leading experts contribute a philosophical introduction, translation, commentary, and scholarly essays on the nature of Diogenes's report as well as core questions in recent research on skepticism.